2019
DOI: 10.1111/poms.12984
|View full text |Cite
|
Sign up to set email alerts
|

Supplier Development and Integration in Competitive Supply Chains

Abstract: S upplier development and supplier integration are two deeply interconnected strategic tools that manufacturers often employ to improve the efficiency and competitiveness of their supply chains. This paper studies the interaction of these two strategic decisions in a competitive environment. Specifically, we consider a duopoly model where two supply chains, each consisting of one manufacturer and one supplier, sell substitutable products in the market. Each manufacturer orders components from its supplier and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…They showed that the investment strategy of the assembler is either zero or full support. Jin, Hu, Kim, and Zhou (2019) looked at two competing supply chains in which each manufacturer can invest in the cost reduction of its own supplier. They assumed that the manufacturer can integrate with the suppliers and showed that this strategy increases the development investment of manufacturers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that the investment strategy of the assembler is either zero or full support. Jin, Hu, Kim, and Zhou (2019) looked at two competing supply chains in which each manufacturer can invest in the cost reduction of its own supplier. They assumed that the manufacturer can integrate with the suppliers and showed that this strategy increases the development investment of manufacturers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This feature together with demand correlation allows us to derive managerial insights Qi, Ahn, and Sinha: Capacity Reservation in a Shared Supplier Production and Operations Management 28(11), pp. 2823-2840, © 2019 regarding the practices in using the different reservation contracts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whent [ að1 À bÞ 1 À ab , the outcome is similar with the upper left region (0, 2H) replaced by (L, 2HÀL).Qi, Ahn, and Sinha: Capacity Reservation in a Shared SupplierProduction and Operations Management 28(11), pp. 2823-2840, © 2019 Production and Operations Management Society (iii) whenĉ e ðc t ; b;tÞ \ c e ,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suppliers' cooperation with downstream manufacturers in technology investments is becoming an effective way to improve the performance of the supply chain (Qi et al, 2015;Jin et al, 2019;Liu and Wang, 2019). In the semiconductor industry, when downstream manufacturers launch new products which need a large number of key components, suppliers need to absorb significant technology investments to improve production technology and expand production capacities of key components.…”
Section: Introductionmentioning
confidence: 99%